JOMS: Ke arah e-pengurusan dalam penerbitan jurnal - Zaibon, Syamsul Bahrin (Fakulti Komunikasi dan Bahasa Moden, Universiti Utara Malaysia, 2004)
Journal publishing is a complex activity. Current journal publishing process flow is fully conducted manually. This kind of method takes a lot of times and workload. Thus, the journal publishing will be late to deliver. Accordingly, JOMS is proposed to facilitate management activities in journal publications. JOMS is an acronym for Journals’ Online Management System which is an innovative and productive e-management approach to replace the current process flow. This paper discussed the current status of JOMS development and its unique characteristics to support journal management committee. With JOMS process flow, the journal publishing process will give advantages in terms of process efficiently, more quickly and reducing committee workload.